The Effectiveness of English Kids’ Song in Listening Comprehension for 5th Grade Elementary School - Nurazizah, Siti Aulia; Atmowardoyo, Haryanto; Muhalim, Muhalim (Journal of Excellence in English Language Education, 2026)
Listening is a crucial skill that is frequently used in mastering a second language. It is widely recognized that many students struggle to develop their Listening Comprehension. This study highlights the effectiveness of English Kids’ songs in improving Listening Comprehension. The researcher employs a quantitative method, using a sample of 30 fifth-grade students from SDN 5 Sungguminasa, selected through a convenience sampling technique. The instruments used in this study were a pre-test and a post-test, involving two groups: an experimental group and a control group, each consisting of 15 students. In the experimental group, students were given treatment, specifically using English Kids’ songs in the English learning process, to assess the effectiveness of the songs in improving Listening Comprehension. Meanwhile, the control group did not receive the treatment being tested, but instead, they followed the standard teaching method already in place. This allowed the researcher to compare the differences between the experimental and control groups. The data were analyzed using an independent t-test with SPSS version 22 to determine the effectiveness of kids’ songs in improving Listening Comprehension. The researcher obtained a significant result of 0.013 < 0.05, indicating that there was a difference between the students who used English kids’ songs to improve their Listening Comprehension and those who used the standard teaching method at SDN 5 Sungguminasa.